Distributed resilient control against denial of service attacks in DC microgrids with constant power load - Chen, Xia; Zhou, Jianyu; Shi, Mengxuan; Chen, Yin; Wen, Jinyu (Renewable & sustainable energy reviews, 2022)
Recent events have shown that cyber attacks are becoming real threats to the power system reliability and resiliency, and there is no exception to the DC microgrids which would become popular in the future. Currently, most secondary controls in DC microgrids heavily rely on communications, making them specifically vulnerable to cyber attacks. This paper presents a resilient distributed control based on the average consensus algorithm and the proportional-integral (PI) consensus algorithm to enhance the system resilience against denial of service attacks and improve the microgrid stability, particularly in the presence of constant power loads. The proposed control casts the average voltage restoration problem into an optimization problem, and because of this, the voltage control is immune to the communication damage caused by malicious denial of service attacks. Moreover, the small-signal stability model of the DC microgrid with distributed energy storages and constant power loads is established, and the impacts of varying constant power loads, controller parameters and communication topology on the system stability are analyzed. Simulations are conducted to verify the effectiveness of the proposed method. •Global voltage and current regulations are realized by distributed mechanisms.•Distributed controllers can keep the DC microgrids stable during cyber-attacks.•Proportional-integral consensus based controllers can recover from Denial of Service attacks.•Distributed controllers contribute to improving stability in the presence of constant power loads.